Liberia : Public Expenditure and Financial Accountability (PEFA) Assessment. (IMF Staff Country Reports; Country Report ;, 2012)
At the request of the Government of Liberia (GoL), the IMF Fiscal Affairs Department (FAD) led an external assessment of the central government's public financial management (PFM) systems based on the Public Expenditure and Financial Accountability (PEFA) methodology. The assessment was undertaken in close collaboration with the Ministry of Finance's (MoF) PFM Reform Coordination Unit (RCU), with the participation of staff of the African Development Bank and the World Bank, and with financial support from the European Union and Sida. The assessment examines progress since the PEFA assessment of 2007 and provides a renewed baseline for monitoring progress in PFM reform and for supporting the GoL in refining, where necessary, the current PFM reform strategy. The assessment snapshot date was April 23, 2012. The report was reviewed by the GoL, the PEFA Secretariat, a donor reference group, and FAD, the latter being at the same time responsible for quality assurance.